Design of IEEE-754 single precision FPU for statistical engine of DNA sequences alignment accelerator: article - Jamil, Mohammad Izzuddin; Abdul Kadir, Rosmalini; Husin, Hanim (2011)
This paper presents the design of single precision IEEE-754 floating point arithmetic operation for statistical engine of DNA sequence alignment accelerator using. The objective of this paper is to construct the arithmetic module for statistical engine of DNA sequence alignment accelerator. This paper is focusing on the single precision IEEE-754 floating point arithmetic which is addition, subtraction and multiplication. The design is written in Verilog language and the tools used are Xilinx ISE 12.1 for coding and Isim 12.1 for the simulation. The module is successfully design and simulate.